Proses Pemerolehan Bahasa Arab Berperspektif Gender Sebagai Bahasa Kedua di Fakultas Tarbiyah dan Ilmu Keguruan IAIN Bukittinggi - Zikrawahyuni Maiza (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
Language has long been considered as a territory dominated by women. For example, in the area of interpretation/translation it can be seen that there are more women than men 3 to 1, and when talking about language teaching, there are more female instructors than men. So the question is: are women better at learning languages and acquiring languages than men? This research was conducted on students of the Arabic Language Study Program of IAIN Bukittinggi. Gender studies related to second language acquisition are linked to developments in two different subfields, namely: second language acquisition studies on one side and language and gender studies on the other. This research is a qualitative descriptive study and uses a performance analysis approach. The results of this study indicate that there are differences in the mastery of syntax and writing of Arabic words and letters between students and female students and there is a gender effect in acquiring and mastering Arabic as a second language.